Plasma atropine concentrations associated with decreased intestinal motility in horses - Ekstrand, Carl; Michanek, Peter; Gehring, Ronette; Sundell, Anna; Källse, Annika; Hedeland, Mikael; Ström, Lena (Frontiers in Veterinary Science, 2022)
Introduction: Atropine is an essential part of the treatment protocol of equine uveitis. Topical atropine administration has been associated with decreased intestinal motility and abdominal pain in horses. Experimental studies have indicated that frequent dosing is associated with higher risk than dosing every six hours. Unfortunately, no quantitative pharmacodynamic data for inhibition of the equine gut are published. Material and methods: Eight standardbred horses were assigned to receive either atropine or saline (control) to be infused over 30 minutes in a two treatment cross-over design. Atropine concentrations in plasma was measured using ultra-high-performance liquid chromatography – tandem mass spectrometry. Intestinal motility was measured using borborygmi frequency and electrointestinography (EIG). Experimental data were analysed using a non-linear mixed effects model. The model was then used to simulate different dosing regimens. Results: Atropine significantly decreased borborygmi response and EIG response. Six horses developed clinical signs of abdominal pain. The pharmacokinetic typical values were 0.31 L/kg, 1.38 L/kg, 0.69 L/kg and 1.95 L/kg·h for the volumes of the central, the highly perfused and the scarcely perfused compartments and the total body clearance, respectively. The pharmacodynamic typical values were 0.31 µg/L, 0.6 and 207 nV2/Hz for the plasma concentration at 50 % of the maximum response, the maximum response and the baseline of caecal EIG response, respectively. Six different dosing regimens of topical atropine sulfate to the eye (0.4 and 1 mg every hour, every 3 hours and every 6 hours) were simulated. Conclusion: The IV PK/PD data coupled with Ssimulations show predict that administration of 1 mg of topical atropine sulfate administered to the eye every hour or every three hours will lead to atropine accumulation in plasma and decreased intestinal myoelectric activity. Administration every six hours offeredpredicted an apparently safe dosing regimen in full sized horses. Clinical studies would be valuable to confirm the conclusions. For smaller equids and horses put at risk for colic due to other causes, droplet bottles that deliver 40 µL 1 % atropine sulfate per drop or less may be used to lower the risk further.